Prevention of bacterial vaginosis, vaginitis and acute inflammation in women with chronic inflammation of the urinary tract - Yu E Dobrohotova; I Yu Ilina; R F Nurullin (IP Berlin A.V., 2014)
Normal microflora of the genital tract of healthy women of reproductive age has a different species composition represented by a wide range of microaerophiles, facultative and obligate anaerobes. Lactobacilli play an important role in maintaining the normal vaginal biocenosis. In patients with chronic inflammatory diseases of the urinary tract above the risk of nonspecific vulvovaginitis. Inclusion of oral probiotics in the treatment regimen of inflammatory diseases of the urinary tract can significantly improve outcomes and reduce the number of relapses.